Macrosomia: a new formula for optimized fetal weight estimation - Hart, Nicola Caroline; Hilbert, A.; Meurer, B.; Schrauder, M.; Schmid, M.; Siemer, Jörn; Voigt, M.; Schild, R. L. (Ultrasound in obstetrics & gynecology, 2010)
Objectives To develop and test a specific formula for estimating weight in the macrosomic fetus. Methods Ultrasound estimations of fetal weight were carried out within 1 week of delivery in 424 singleton fetuses with a birth weight of ≥ 4000 g. Exclusion criteria were multiple pregnancy, intrauterine death and major structural or chromosomal anomalies. Stepwise regression modeling was used to derive a prediction formula with birth weight as the dependent variable and maternal booking weight and fetal biometric measurements as independent parameters. After a new formula for estimated fetal weight (EFW) had been developed in a formula-finding group (n = 284), it was compared with commonly used weight equations (evaluation group, n = 140). Results The new formula (logeEFW = 7.6377445039 + 0.0002951035 × maternal weight + 0.0003949464 × head circumference + 0.0005241529 × abdominal circumference + 0.0048698624 × femur length) proved to be superior to established equations, with the smallest mean error (mean ± SD, −10 ± 202 g), the smallest mean percentage error (mean ± SD, −0.03 ± 4.6%) and the lowest mean absolute percentage error (3.69 (range, 0.05-13.57)%) when studied in the evaluation group. With the new formula, 77.9% of estimates fell within ± 5% of the actual weight at birth, 97.1% within ± 10%, and 100% within ± 15% and ± 20%. Conclusions The new formula allows better weight estimation in the macrosomic fetus. Copyright © 2009 ISUOG. Published by John Wiley & Sons, Ltd.